2016
DOI: 10.1007/s10803-016-2775-8
|View full text |Cite
|
Sign up to set email alerts
|

Training the Motor Aspects of Pre-driving Skills of Young Adults With and Without Autism Spectrum Disorder

Abstract: The purpose of this study was to investigate the utility of using a driving simulator to address the motor aspects of pre-driving skills with young adults with Autism Spectrum Disorder (ASD). A group of neurotypical control participants and ten participants with ASD completed 18 interactive steering and pedal exercises with the goal to achieve error-free performance. Most participants were able to achieve this goal within five trials for all exercises except for the two most difficult ones. Minimal performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…A post hoc analysis suggests that experience level does not appear to significantly affect these rates of turning-related errors. It is possible that motor coordination difficulties as well as attentional differences both contributed to error rates, as recent investigations of motor coordination differences between drivers with and without ASD have shown that drivers with ASD require significantly more time than controls to perform steering-related tasks (Cox et al 2016; Brooks et al 2016). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A post hoc analysis suggests that experience level does not appear to significantly affect these rates of turning-related errors. It is possible that motor coordination difficulties as well as attentional differences both contributed to error rates, as recent investigations of motor coordination differences between drivers with and without ASD have shown that drivers with ASD require significantly more time than controls to perform steering-related tasks (Cox et al 2016; Brooks et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (2012) reported that a majority (51.1%) of children with ASD of driving age also had ADHD; however, this factor did not significantly affect whether or not the child drove a vehicle. Brooks et al (2016) reported that 9 of 10 participants in a group of individuals with ASD were also diagnosed with ADHD compared to only 4 of 31 having ADHD in the control group. Thus, future work is needed to understand the potential impact of ADHD on driving simulation performance for individual with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autism Spectrum Disorder (ASD) is a neurodevelopmental condition, which is associated with impairment of communication and social interaction, along with executive function deficits affecting working memory, motor coordination, attention, planning, mental flexibility, and visual perception [34,35]. It has a worldwide prevalence of 0.6-2% [36] and is often comorbid with ADHD.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…The reasons for using a driving simulator for one study were that the simulator allowed drivers to safely focus on one skill at a time without the need to engage in other driving tasks simultaneously and driving task complexity could be introduced incrementally. Skills practised were upper body and lower body motor skills (Brooks et al, 2016). The driving simulator in the Wade et al (2016) study was used because it could be adapted to the specific learning needs of people with ASD by providing Full-text articles assessed for eligibility (n = 126)…”
Section: Interventions Incorporating Simulatorsmentioning
confidence: 99%